2015
DOI: 10.3109/17435390.2015.1048325
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte adhesion induced by multi-walled carbon nanotubes and palmitic acid in endothelial cells and alveolar–endothelial co-cultures

Abstract: Free palmitic acid (PA) is a potential pro-atherogenic stimulus that may aggravate particle-mediated cardiovascular health effects. We hypothesized that the presence of PA can aggravate oxidative stress and endothelial activation induced by multi-walled carbon nanotube (MWCNT) exposure in vitro. We investigated the interaction between direct exposure to MWCNTs and PA on THP-1 monocyte adhesion to human umbilical vein endothelial cells (HUVECs), as well as on indirect exposure in an alveolar-endothelial co-cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 49 publications
3
21
1
Order By: Relevance
“…However, it is expected that BSA or LNA will show similar effects on the hydrodynamic sizes and Zeta potential of ZnO NPs when added into the cell culture medium. Previously, it was shown that the salt of SFA or SFA complexed to BSA may coat NPs, showing as altered hydrodynamic sizes and/or zeta potential of NPs [10,11,12,13]. The results from the present study further indicated that the presence of BSA or LNA complexed to BSA could coat ZnO NPs and, consequently, stabilize the NPs.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…However, it is expected that BSA or LNA will show similar effects on the hydrodynamic sizes and Zeta potential of ZnO NPs when added into the cell culture medium. Previously, it was shown that the salt of SFA or SFA complexed to BSA may coat NPs, showing as altered hydrodynamic sizes and/or zeta potential of NPs [10,11,12,13]. The results from the present study further indicated that the presence of BSA or LNA complexed to BSA could coat ZnO NPs and, consequently, stabilize the NPs.…”
Section: Discussionsupporting
confidence: 74%
“…For example, the presence of a typical saturated fatty acid (SFA), palmitic acid (100 µM) promoted multi-walled carbon nanotube-mediated adhesion of THP-1 monocytes onto human endothelial cells without an effect on production of the intracellular reactive oxygen species (ROS) or depletion of glutathione (GSH) [10]. In contrast, co-exposure to 200 µM palmitate and ZnO NPs did not significantly affect THP-1 monocyte adhesion, but induced higher cytotoxicity to human endothelial cells due to combined toxicity of palmitate and ZnO NPs [11].…”
Section: Introductionmentioning
confidence: 99%
“…ICAM‐1, VCAM‐1 and selectins) have been observed in HUVECs after exposure to a variety of NPs, including carbonaceous NPs (CB NPs and carbon nanotubes) (Vesterdal et al, ; Cao et al, , ), metal‐based NPs (Ag, ZnO and TiO 2 NPs) (Li et al, ; Montiel‐Davalos et al, ; Shi et al, ; Suzuki et al, ; Danielsen et al, ;) and silica NPs (Corbalan et al, ; Duan et al, ; Guo et al, ). Some studies also showed increased monocyte adhesion to NP‐exposed HUVECs, which is in agreement with the increased expression of adhesion molecules (Danielsen et al, ; Cao et al, ; Cao et al, ; Shi et al, ; Suzuki et al, ). However, it should be noticed that monocyte adhesion to HUVECs is not always correlated with the expression of adhesion molecules.…”
Section: Toxic Effects Of Nps To Huvecsmentioning
confidence: 99%
“…Besides proteins, the interactions between NPs and excessive nutrients may also need further investigations (Cao et al, ). For example, it has been shown that the presence of palmitic acid, a saturated fatty acid, coated MWCNT and promoted MWCNT‐induced monocyte adhesion to HUVECs without an effect on oxidative stress (Cao et al, ). In our recent study, we showed that the presence of palmitate could coat ZnO NPs but did not significantly affect ZnO NP‐induced monocyte adhesion or the release of inflammatory cytokines in HUVECs.…”
Section: Factors To Influence the Responses Of Huvecs To Np Exposurementioning
confidence: 99%
“…This approach is common in toxicological studies on primary cell cultures. For instance, we have used pooled batches of endothelial cells from several donors for studies on liposomes and carbon nanotubes [58][59][60]. The flow cytometry-based detection of ROS production in blood samples can be further developed for investigations of interindividual differences in response to NMs in healthy individuals, susceptible groups or patients with specific diseases.…”
Section: Discussionmentioning
confidence: 99%